IMPROVING ENGLISH SPEAKING SKILL OF EFL CLASS BY USING VIDEO BLOG ON SOCIAL MEDIA - Yulima Melsipa Lingga; Wan Yuliyanti; Yuliana Ningsih (Universitas Galuh, 2021)
This research aims to investigate the improvement of English speaking skill in the first year students by using video blog on social media. This research is conducted at Politeknik Negeri Tanah Laut in April to July 2020 located in the District of Pelaihari, Tanah Laut Regency, South Borneo. The object of this research is the first year students in class 1C and 1D of the Information Technology department. There are 65 students. As for collection of the data based on the CAR methods are planning, action and observation, and reflection. While the technique of collecting the data is qualitative data with interview transcripts and class observation. The students were asked to make video blog to investigate their capability in English speaking skill. The results showed that in cycle 1 found that the frequency level of proficiency criteria of the students are still in average level in vocabulary and pronunciation, and poor level in grammar, fluency and content. In cycle 2, the frequency levels become better. All criteria increase at good level. Video blog on social media improves the English speaking skill of the students well.